MENINGKATKAN KECERDASAN VISUAL SPASIAL ANAK MELALUI BERMAIN PUZZLE PADA KELOMPOK B3 DI TK PEMBINA NEGERI 1 BANGKO KABUPATEN ROKAN HILIR - Norhayati, Norhayati; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Backgroud in this study was less the increase in the child’s visual-spasial intelligence puzzle, the child’s interest in seeing color, shape, size and media to observe the puzzle and the lack of application of the puzzle to help the visual-spatial intelligence of the child. Formulation of the problem of this research is : what puzzles can improve visual spatial intelligence of children in kindergarten Pembina State 1 Bangko Rokan Hilir. How can thechers to improve visual intelligence though play puzzle child in kindergarten Pembina State 1 Bangko Rokan Hilir. How high is the increase in visual-spatial intelligence through play puzzle child in kindergarten Pembina State 1 Bangko Rokan Hilir. This study aims to determine the puzzles can improve visual spatial intelligence of children in kindergarten Pembina State 1 Bangko Rokan Hilir. To find out how teachers in improving visual-spatial intelligence though play puzzle child in kindergarten Pembina State 1 Bangko Rokan Hilir. To know the high increase in visuals-spatial intelligence though play puzzle child in kindergarten Pembina State 1 Bangko Rokan hilir. This study research is a class act done in two cycles, data collection tools used in this research is observation sheet. This study is the number of 17 children were taken from the results of the evaluation of the data at the end of ech cycle based on the results obtained percentage increase in the first cycle is 52.45% and increased to 73.53% the second cycle can be concluded spatial intelligence of the child at the age of 5-6 years.Keywords: Visual Spatial Intelligence, Play Puzzle